Digital International Relations - Baykov, Andrey; Zinovieva, Elena (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
The book is the beginning of new interdisciplinary research series at the intersection of international relations, diplomacy, law, economics, and politics on the basis of global digital transformation. Digital international relations form a new mode of interaction between states and in terms of solving the most pressing problems of modernity. Law, economics, diplomacy and education are selected as key areas of human activity that can become the sphere of perspective research of digital international relations. This book will interest diplomats, scholars of international relations, and of international law. Andrey Baikov is an associate professor of political science at MGIMO, the Russian diplomatic school. Elena Zinovieva teaches international relations at MGIMO.
Introduction: Political Order of Digital State -- Part I. Digital Transformation of Global Politics: Key Directions of the Analysis -- Chapter 1. The Practice of the Sovereignty in the Age of Digitalization -- Chapter 2. The Problem of Developing Scientific and Technological Potential in the Context of the Russian-American Confrontation: from the "Nuclear Triad" to the Competition of Innovative Systems -- Chapter 3. Ethical Approaches to AI in Russia, the USA and China -- Chapter 4. Indian Innovation Policy in the Context of Modern Geopolitics -- Chapter 5. Internet Governance in BRICS -- Chapter 6. On the Experience of the ASEAN Regional Forum on Security in the Field of Developing Confidence-Building Measures in the Information Space -- Chapter 7. Application of Network Data Analysis in Studies of Informal Parliamentary Groups -- Part II. Legal Support for the Development of the Digital Economy -- Chapter 8. General Issues of Digitalization and its Impact on the Legal Regulation of Public Relations -- Chapter 9. International Law in the Age of Digitalization -- Chapter 10. Criminal Law in the Age of Digitalization -- Chapter 11. Financial Law in the Age of Digitalization -- Chapter 12. Tax Law in the Age of Digitalization -- Chapter 13. Labour Law in the Age of Digitalization -- Chapter 14. Commercial Law in the Age of Digitalization -- Chapter 15. Banking Law in the Age of Digitalization -- Chapter 16. Administrative Law in the Age of Digitalization -- Chapter 17. Intellectual Property Law in the Age of Digitalization -- Part III. Digital Transformation of Global Economics -- Chapter 18. Russian Business in the Sector of International Information Security: the Formation of a New Agenda -- Chapter 19. European Regulation of Internet Platforms: Problems and Prospects -- Chapter 20. Digital Transformation of the EAEU financial sector -- Chapter 21. Digitalization of the World Agricultural Markets -- Chapter 22. Information Support of the Energy Market in the Context of Digitalization -- Chapter 23. Digital Transformation of Chemical Industry' Companies -- Chapter 24. Eurasian Industrial Performance: Sustainable and Digital Aspects -- Chapter 25. Digitalization of Labour Market -- Chapter 26. Digitalization of Insurance: New Risks -- Chapter 27. Digital Technologies for Visualizing Economic History as a Tool for Educational Diplomacy -- Part IV. Educational and Scientific Diplomacy in the Age of Digitalization -- Chapter 28. Comparison of the Effectiveness of Certain Types of Work in the Process of Distance and Traditional Training of International Economists -- Chapter 29. The Role of Digital Technologies in Learning a Foreign Language in the Context of the Lifelong Education Paradigm -- Chapter 30. Media Data. Technological Challenges and Prospects -- Part V. International Transport and Global Transport Policy in the Context of Digitalization -- Chapter 31. Digital Transformation and Global Transport Platform: Bringing together International Business Entities into Integrated Supply Chain -- Chapter 32. Intelligent Transport Systems and Its Role in the Implementation of Global Transport Policy in the Context of Digitalization -- Chapter 33. Electronic Document Management in Transport Sector: the Realities of Modernity -- Chapter 34. Tasks and Challenges for the Russian System of International Goods Delivery in the Context of Digitalization -- Chapter 35. Transport Engineering of the EAEU and Digitalization -- Conclusion. The Future of Digital International Relations. .
Keywords: Diplomacy; Political science; Law and economics; Diplomacy; Politics and International Studies; Law and Economics